Skilled attendance at delivery in Bangladesh: a strategy development tool - Chowdhury, AMR; Mahbub, Amina; Chowdhury, Anita Sharif; Kamal, Faiza Ela; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
SAFE study aimed to provide new knowledge on the identification, implementation and evaluation of effective, affordable and equitable strategies to increase Skilled Attendance at delivery in developing countries. It was a multi country research and five countries .. including Bangladesh were involved in this study. The main purpose of SAFE study was to develop a Strategy Development Tool (SDT), which would enable the policy makers and programme planners to systematically gather and interpret information on skilled attendance at delivery. The SDT contained five components, which revealed the collection, analysis and synthesis of existing and new data on skilled attendance. The five modules were: problem identification, situation analysis, needs assessment, quality of clinical care and synthesis. The cost of the application of the SDT was also examined during SAFE study as part of the field test to consider the affordability. In Bangladesh under SAFE study using the SDT, certain strategy options to promote skilled attendance at delivery were developed. The key findings in SAFE study and the strategy options are given in the following. A review of existing literature showed that in Bangladesh only 7% of deliveries were assisted by qualified medical practitioners, while 22% by relatives and almost half by traditional birth attendants (TBAs). At community level where home delivery was almost universal certain factors were related to skilled attendance at delivery: mother's age and education, religion, residence poverty status and child's birth order. It was found that proportion of deliveries done at health facilities were highly inequitable. Whereas the proportion of well-to-do women delivering in a facility was 17.3 percent, it was less than one percent for the poorest women. DHS 1 data (1999-'00) revealed that women who had used health facilities for other health services like immunisation, contraception, and antenatal care (ANC) in the past used health facilities for deliveries more frequently compared to others. DHS data also showed that the proportion delivered at a Govt. Hospital increased by four times who had 4+ ANC visits, but the need assessment study reve~led that ANC during pregnancy was not that considered important by the women for the purpose of delivery; The need assessment study also identitied a number of barriers at different levels which hindered women's access to fomlal deiivery care. At individual level women were not , willing to deliver in the hospital due to shame, fear of caesarean and death. At family level it was noted that the major decision makers i.e. mothers-in-law, husbands were the least knowledgeable about different level of obstetric services, which eventually increased the expenditure of delivery care. In the need assessment study, the villagers pointed out that in emergencies the neighbours extended their cooperation. However, as most of them were poor, often it was difficult for them to provide financial support or loans. Thus, economic constraints were noted as one of the major hindrances in accessing fonnal delivery care services. At community level it was found that neighbours discouraged to go to the health facilities for delivery care and over dependence on TBAs was also noted. The key informants pointed out that although many NGOs in Bangladesh had motivational activities at community level, but those were not adequate for promoting skilled attendance. The study revealed that at facility level unfriendly behaviour of the healthcare providers, lack of female doctors and problems in the system of referral prevented people's access to formal delivery care The study indicated that doctors at Upazila (sub district) level mostly did not have specialised obs & gynae training, which limited service provision. The qualified health care providers were found to be concentrated in the urban areas and few female doctors could be found in rural areas. Most of the key informants opined that lack of professional commitment was a major problem in promoting skilled attendance in Bangladesh. The doctors posted at the Upazilas were mostly found not to reside in the campus and were more interested in private practice.